Der Einfluß der Temperatur auf die Entwicklung der Kleinen Fichtenblattwespe, Pristiphora abietina (Christ), im Kokon (Hymenoptera: Tenthredinidae). - Ohnesorge, Bernhart (Contributions to Entomology = Beiträge zur Entomologie, 1960)
In the course of development of Pristiphora abietina (Christ) in the cocoon there are recognisable two phases with different reaction to environmental temperatures. The temperature optimum of the first phase is about 7-10°C, that of the second one 20-21°C. The author discusses the question wether the first phase of nymphal development could be regarded as a case of true diapause, the species in question claiming the same temperature like diapausing insects use to do, but the morphological development, however, does not stop during this time. The ecological purpose of the low optimum of temperature during the first phase is probably the coordination of the phenology of Pr. abietina with its host plant.